Pengaruh Minat Belajar Siswa terhadap Prestasi Belajar Siswa pada Subtema 2 Kebersamaan dalam Keberagaman di Kelas IV SD Negeri Marubun Jaya - Sri Rezeki Butarbutar; Lisbet N. Sihombing; Eva Pasaribu (Tematik: Jurnal Penelitian Pendidikan Dasar, 2022)
This study aims to determine (1) Knowing student’s interest in learning, (2) Knowing stundent learning achievment The implementation of learning in this study applies thematic learning on Theme 1 The Beauty of Togetherness Sub-theme 2 Togetherness in Diversity which efforts to increase are carried out by providing interest in learning to these students. The sample in this study were students of class IV-B as many as 30 students. Methods of collecting data using questionnaires and tests. Data analysis techniques used normality tests and hypothesis testing. After being analyzed, the results of the t-test hypothesis test obtained tcound 2,451 and tube 1,701 with a significant value of 0,021 < 0,05, it can be concluded that there is a positive and significant influence between student interest in learning and student achievement.